Seasonality in Regression: An Application of Smoothness Priors - Mark Gersovitz; James G. MacKinnon (Queen's University, Department of Economics, 1977)
This article argues that conventional approaches to the treatment of seasonality in econometric investigation are often inappropriate. A more appropriate technique is to allow all regression coefficients to vary with the season, but to constrain them to do so in a smooth fashion. A Bayesian method of estimating smoothly varying seasonal coefficients is developed, based on Shiller's (1973) approach to estimating distributed lags. In a sampling experiment, this technique outperforms ordinary least squares by a substantial margin. An application of this technique to the estimation of the demand for soft drinks is also presented.
Keywords: C10; C11; C13; 330; seasonality; smoothness prior; distributed lag; mixed estimation; soft drinks